(untitled) (Revista Brasileira Multidisciplinar, 2008)
This paper analyzes the main economic, politic and social changes that happened in Brazil in the 90’s due to the hegemony of the neoliberal thought that offered an opportunity to a series of reforms, not only economical as well as politic and social ones, that caused the weakness of the State in benefit of a new governorship managed by the market forces and impelled by the financial and commercial globalization. In this period, when the Brazilian State abandoned his articulator role of social and economical development policies, this space has come to be occupied by states and municipal districts that started to articulate development policies and to negotiate, directly with transnational companies, productive investments for their areas without possessing an efficient technical body to drive the negotiations. The final result was a series of agreements that benefitted mainly the transnational companies, casting doubts about the benefits that countries, such as Brazil, had with the intensification of the globalization in the 90’s.